2020
DOI: 10.3201/eid2607.200275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Argentine Hemorrhagic Fever using Ribavirin and Favipiravir, Belgium, 2020

Abstract: A rgentine hemorrhagic fever (AHF) is a severe hemorrhagic fever caused by a New World arenavirus, Junin virus (JUNV), which was discovered in 1958 (1). The virus reservoir consists of rodents found in humid pampas in South America. The endemic area covers 150,000 km 2 distributed over 4 provinces in Argentina; ≈5.6 million persons are at risk (2). Until 1992, the year when a prophylactic vaccine was introduced, annual outbreaks affected mainly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In clinical practice, FPV has been reported for treatment of human infections with life-threatening hemorrhagic fever virus, such as Ebola virus [18] , Lassa virus [19] , Arenavirus [20] and SFTSV [15] , but only limited to case report or case series report with very small case number. Despite of FPV treatment benefit shown in the most recent RCT of SFTS [14] , the result was obtained under near-ideal test conditions in highly selected patient populations, for whom the behavior of patients and investigators are highly compliant and adherent, and non-representative of routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, FPV has been reported for treatment of human infections with life-threatening hemorrhagic fever virus, such as Ebola virus [18] , Lassa virus [19] , Arenavirus [20] and SFTSV [15] , but only limited to case report or case series report with very small case number. Despite of FPV treatment benefit shown in the most recent RCT of SFTS [14] , the result was obtained under near-ideal test conditions in highly selected patient populations, for whom the behavior of patients and investigators are highly compliant and adherent, and non-representative of routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2 During the peak of the epidemic in Belgium, FVP was considered as an antiviral therapeutic option in our institution for the following reasons: (1) restricted access to remdesivir in Belgium; (2) low frequency of side-effects 4 ; (3) direct availability; and (4) our previous experience with FVP therapy in the management of Argentine Hemorrhagic Fever. 5 Here is reported the tolerability of FVP therapy in four critically ill patients.…”
Section: Tolerability Of Favipiravir Therapy In Critically Ill Patienmentioning
confidence: 94%
“…It is a derivative of pyrazinecarboxamide as well as other antiviral drugs including T-1105 and T-1106 ( Zhu et al, 2018 ). Experimental studies had shown that favipiravir was effective against influenza viruses ( Pascua et al, 2019 ), yellow fever virus ( Furuta et al, 2013 ), foot and mouth disease virus ( Furuta et al, 2009b ), West Nile virus ( Escribano-Romero et al, 2017 ), arenaviruses ( Veliziotis et al, 2020 ), bunyaviruses ( Scharton et al, 2014 ) and alphaviruses ( Delang et al, 2014 ), enteroviruses ( Furuta et al, 2013 ), Rift Valley fever ( Borrego et al, 2019 ) and other flaviviruses ( Segura Guerrero et al, 2018 ).…”
Section: Rna Polymerase Inhibitorsmentioning
confidence: 99%